2020
DOI: 10.1186/s40634-020-00229-7
|View full text |Cite
|
Sign up to set email alerts
|

No differences in knee kinematics between active and passive flexion-extension movement: an intra-operative kinematic analysis performed during total knee arthroplasty

Abstract: Purpose: The objective of the present study was to acquire and compare by the use of a navigation system the intra-operative flexion-extension movement of the knee performed actively by the patient and passively by the surgeon before and after a total knee arthroplasty (TKA) implantation. Methods: A cohort of 31 patients with primary knee osteoarthritis (OA), candidate for TKA underwent intraoperative kinematics assessment with a commercial navigation system before and after the definitive implant positioning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Moreover, in a radiological investigation, Masri and McCormack reported, that quadriceps contraction does not alter the congruence angles obtained in 30° and 45° axial views [ 28 ]. Additionally, Grassi et al showed, that there were no differences in knee kinematics between active and passive flexion–extension movement cycles regarding intra-operative kinematic analysis [ 29 ]. Therefore, our results should reflect on comparable native patellar tracking in this experimental setup.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a radiological investigation, Masri and McCormack reported, that quadriceps contraction does not alter the congruence angles obtained in 30° and 45° axial views [ 28 ]. Additionally, Grassi et al showed, that there were no differences in knee kinematics between active and passive flexion–extension movement cycles regarding intra-operative kinematic analysis [ 29 ]. Therefore, our results should reflect on comparable native patellar tracking in this experimental setup.…”
Section: Discussionmentioning
confidence: 99%
“…For the ROM data taken from physical therapy notes in Dataset 3, more than 90% of patients achieved at least 90° of flexion at the last recorded ROM measurement (93.6%). While data reported in this study is PROM, the difference between AROM and PROM has been reported to be small in previous studies of total knee arthroplasty patients [ 29 31 ]. The largest difference between AROM and PROM in these studies was 4%.…”
Section: Discussionmentioning
confidence: 69%
“…First, regarding anatomical and biomechanical differences, during CAS, knee kinematics are assessed after arthrotomy, passively and without loading, whereas gait kinematics are assessed with a closed knee, actively and with loading and impacts. One recent study suggested that there were no differences between active and passive knee flexion–extension angles after arthrotomy but without loading [ 7 ]. Moreover, good correlations were found between CAS measurements and impact-free weight-bearing knee kinematics assessed using monoplane fluoroscopy six months after surgery [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Grassi et al . recently showed that there were no significant differences between active and passive intra-operative knee kinematics as measured using a CAS system during knee flexion–extension before and after TKA [ 7 ]. Belvedere et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation